Situation Report: Czechoslovakia, 18 December 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Renewed Denunciation of the 1968 Reformers in Czechoslovakia Fuel and Power Problems Czechoslovak-Soviet Co-operation in Iron Ore Extraction The Christmas Market